LEMBAGA PENDIDIKAN ANAK USIA DINI DENGAN METODE MONTESSORI DI BANJARBARU - Putri Indrayanti Fajrin; Dahliani Dahliani (JURNAL TUGAS AKHIR MAHASISWA LANTING, 2021)
Age 0-6 years is a golden period/golden age. In this age range, a child’s brain is like foam which has a high absorption. The right stimulus is the main foundation of its development. One of the right stimulations aside from family for early childhood through Early Childhood Education with the Montessori method. In Early Childhood Education with the Montessori method, children will be given educational services and their rights to grow and develop. The Montessori method has 6 main areas, namely practical life, sensory, mathematics, language, art, and culture. Basically, the Montessori method is already a concept, but it is still too abstract to be directly applied to buildings, so it requires architectural design methods and approaches. The six areas will be applied directly to the building through spatial elements so the design method used is the direct analogy method. This method is used so that children can have direct experience when they interact with their surroundings (experiential). In addition, the Montessori method implements a hands-on-learning system so the children experience it directly. Therefore, a suitable approach is an experiencing architecture.